2021
DOI: 10.3390/ijerph18041876
|View full text |Cite
|
Sign up to set email alerts
|

Global Impact of COVID-19 on Weight and Weight-Related Behaviors in the Adult Population: A Scoping Review

Abstract: Objective: To provide an overview of what is known about the impact of COVID-19 on weight and weight-related behaviors. Methods: Systematic scoping review using the Arksey and O’Malley methodology. Results: A total of 19 out of 396 articles were included. All studies were conducted using online self-report surveys. The average age of respondents ranged from 19 to 47 years old, comprised of more females. Almost one-half and one-fifth of the respondents gained and lost weight during the COVID-19 pandemic, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 37 publications
(218 reference statements)
8
113
2
5
Order By: Relevance
“…The indirect consequences of the pandemic have paradoxically, made the situation even worse as more people have worsened than improved their diets [ 17 ], and less people are as active as they were pre-pandemic, linked to more working from home, so less active travel, as well as anxieties in many individuals in spending time outdoors. There is emerging evidence to suggest pandemic-associated weight gain, potentially more marked in younger people, in women compared to men, and in people from more deprived communities [ 18 •, 19 ].…”
Section: Pandemic Has Likely Worsened Obesity Levelsmentioning
confidence: 99%
“…The indirect consequences of the pandemic have paradoxically, made the situation even worse as more people have worsened than improved their diets [ 17 ], and less people are as active as they were pre-pandemic, linked to more working from home, so less active travel, as well as anxieties in many individuals in spending time outdoors. There is emerging evidence to suggest pandemic-associated weight gain, potentially more marked in younger people, in women compared to men, and in people from more deprived communities [ 18 •, 19 ].…”
Section: Pandemic Has Likely Worsened Obesity Levelsmentioning
confidence: 99%
“…It has been observed that people with obesity presented worsened sleep in lockdown [ 11 ]. A shorter sleep duration is a predictor of weight gain, as suggested in a systematic scoping review [ 12 ]. Moreover, those with negative changes in sleep quality reported more weight gain than those with positive changes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight changes can be both beneficial and detrimental to health and wellbeing, and understanding the factors associated with these changes is crucial for the development of targeted interventions. Increased HFSS food intake, snacking and alcohol consumption have all been previously identified as important predictors of initial pandemic weight/BMI gain [7,9,10,12,[18][19][20][21]25]. Studies in the UK and internationally report large inter-individual variability in dietary changes as a result of the COVID-19 pandemic [46], which in turn have been associated with weight change [7,12,14].…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…However, reports also suggest that despite significant proportions of people increasing weight and BMI (11.2-72.4%), many have also decreased weight and BMI (7.2-51.4%) during the start of the pandemic [11][12][13][14][15][16][17]. These initial weight trajectories during COVID-19 are associated with several socio-demographic, COVID-19-related and behavioural factors including age, gender, initial BMI, pandemic living and working conditions, diet, physical activity and alcohol intake [7,9,10,12,[18][19][20][21]. Short-term shifts in health behaviours can result in small, yet meaningful changes in bodyweight, as seen with seasonal holiday weight gain during the winter months, which accounts for a large proportion of annual weight gain [22,23].…”
Section: Introductionmentioning
confidence: 99%